2013
DOI: 10.1103/physrevb.87.174511
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity of disordered Dirac fermions

Abstract: We study the effect of disorder on massless, spinful Dirac fermions in two spatial dimensions with attractive interactions, and show that the combination of disorder and attractive interactions is deadly to the Dirac semimetal phase. First, we derive the zero temperature phase diagram of a clean Dirac fermion system with tunable doping level (µ) and attraction strength (g). We show that it contains two phases: a superconductor and a Dirac semimetal. Then, we add disorder, and show that arbitrarily weak disorde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
155
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(165 citation statements)
references
References 55 publications
9
155
1
Order By: Relevance
“…3). It is worth noting that the disorder introduced by Zn doping, while weak, might even, counterintuitively, support superconductivity in this limit 29 . Finally, a subtlety could arise for significant V: In order to avoid onsite and nearest-neighbour repulsion, this could drive a transition from a nodeless B 1u f-wave to a nodal B 2u f-wave 30 , but for realistic values of V this is highly unlikely.…”
Section: Article Nature Communications | Doi: 101038/ncomms5261mentioning
confidence: 99%
“…3). It is worth noting that the disorder introduced by Zn doping, while weak, might even, counterintuitively, support superconductivity in this limit 29 . Finally, a subtlety could arise for significant V: In order to avoid onsite and nearest-neighbour repulsion, this could drive a transition from a nodeless B 1u f-wave to a nodal B 2u f-wave 30 , but for realistic values of V this is highly unlikely.…”
Section: Article Nature Communications | Doi: 101038/ncomms5261mentioning
confidence: 99%
“…Previous theoretical and numerical studies [18,21,22,30] have found that, different from ordinary metals, the Cooper theorem is no longer valid in undoped Dirac semimetals. Because the fermion density of states (DOS) vanishes linearly near the band-touching points, an infinitely weak attraction is not sufficient to bind Dirac fermions together to form Cooper pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Nandkishore et al [30] and Potirniche et al [31] have studied the effects of random chemical potential on superconductivity. The main conclusion reached in the mean-field analysis [30] is that superconductivity is enhanced. In this paper, we will consider the impact of all the three types of disorder.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations